The Influence of Non-Clinical Factors (Age, Location, and Non-Medical Costs) on Patient Satisfaction and Loyalty at The Outpatient Polyclinic of The Manado City Dental and Oral Hospital - Sysilia M. N. Karinda; Windy M.V. Wariki; Aaltje E. Manampiring (CV. Inara, 2026)
Patient satisfaction and loyalty are influenced not only by clinical factors but also by non-clinical factors, especially in the context of dental and oral health services supported by the National Health Insurance system. Three non-clinical factors that are strongly suspected of influencing patient satisfaction are age, non-medical costs, and location. Purpose. This study aims toanalyzing the direct and indirect influence between age, non-medical costs, and location on patient loyalty through patient satisfactionat the outpatient clinic of the Manado City Dental and Oral HospitalMethods. This study is a quantitative study with an analytical observational approach and uses a cross-sectional design, which was conducted in October - December 2025. The study sample consisted of 128 respondents consisting of respondents ≥ 18 years. Data were collected through questionnaires, then analyzed using univariate, bivariate, and multivariate analysis. Results.The results show that there is a direct effect of age and non-medical costs on patient satisfaction (p = 0.001), there is a direct effect of age on patient loyalty (p = 0.001), there is a direct effect of patient satisfaction on patient loyalty (p = 0.001), there is a direct effect of age on patient loyalty through patient satisfaction (p = 0.001) and there is a direct effect of non-medical costs on patient loyalty through patient satisfaction (p = 0.036). Meanwhile, there is no direct effect of location on patient satisfaction and loyalty (p = 0.976 and 0.436), there is no direct effect of non-medical costs on patient loyalty (p = 0.058), and there is no effect of location on patient loyalty through patient satisfaction (p = 0.979).ConclusionPatient satisfaction is a full mediator between non-medical costs and loyalty, and a partial mediator between age and loyalty.